A Não-Identidade no Não-Lugar nas Memórias de Hugo Hamilton (TEL Tempo, Espaço e Linguagem, 2022)
Hugo Hamilton, in The Speckled People and The Sailor in the Wardrobe, explores his complex identity formation within his German and Anglo-Irish family between 1950 and 60. In an attempt to get rid of his identity, the author-character creates a project of non-identity in the non-place. This work analyzes the (im)possibility of such a project and its implications in his identity and history.